Screening for prolonged incubation of HTLV-I infection in British and Jamaican relatives of British patients with tropical spastic paraparesis. Issue 6720 (3rd February 1990) - Cruickshank, J K; Richardson, J H; Morgan, O S; Porter, J; Klenerman, P; Knight, J; Newell, A L; Rudge, P; Dalgleish, A G
Abstract : OBJECTIVE--To compare the prevalence of antibody to and proviral DNA of the retrovirus HTLV-I in relatives of 11 British patients with tropical spastic paraparesis who had migrated from Jamaica before they developed symptoms, and to examine factors possibly related to transmission of HTLV-I. DESIGN--Migrant, family study. Antibody state was determined by several methods and confirmed by western blotting; the polymerase chain reaction was used to detect proviral DNA. SETTING--Britain and Jamaica. SUBJECTS--All available first degree relatives: those born and still resident in Jamaica (group 1); those born in Jamaica who migrated to Britain (group 2); and index patients' children who were born and resident in Britain (group 3). All had been breast fed and none had had blood transfusions. RESULTS--Of the 66 living relatives, 60 were traced. Seroprevalence among those born in Jamaica (irrespective of current residence) was 22% (10/46; 95% confidence limits 9 to 34%) compared with zero among British born offspring (0/14) and was higher in group 2 at 33% (7/21; 12 to 55%) than in group 1 at 12% (3/25; 0 to 25%). (Patients in group 1 had the greatest mean age.) Proviral DNA was not detected in any subject negative for HTLV-I antibody, making prolonged viral incubation in those negative for the antibody unlikely. CONCLUSION--In this sample factors related to place of birth and early residence were more important in transmission of HTLV-I than maternal or age effects. In areas with a low to moderate prevalence policies of preventing mothers who are carriers of the virus from breast feeding would be premature.